Identifying learning techniques among high achievers - P, Shanmukananda; ., L Padma (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In every college, it is noticed that in spite of being exposed to the same teaching modalities and adopting seemingly similar strategies, some students perform much better than their peers. This can be evaluated in the form of better academic performance in the internal assessments they undertake. This project is an endeavor to identify the learning techniques among high achievers which they employ to outperform others. We can also suggest the same to the medium and low achievers so that they can improve their academic performance. This study was conducted to identify different learning techniques adopted by high achievers and suggesting the same to medium and low achievers. Methods: After obtaining clearance from the institutional ethics committee, the high achievers were identified by selecting the upper third of the students in the ascending order of marks obtained in the consecutive three internal assessments in three consecutive batches. The identity of the students was not revealed. They were then administered an open ended questionnaire which addressed relevant issues. The most common and feasible techniques will be suggested to the medium and low achievers. Results: The respondents’ (n=101) replies were analyzed by calculating the percentages of responses, and assessing based on that, which were the most frequently adapted techniques by these high achievers Conclusions: High-achievers have a diligent study pattern; they not only study regularly, but also involve in group discussions and approach their teachers when in doubt. Additionally, they refer to other sources of information like the internet, demonstrating a proactive attitude towards studies.